Ahistorisitas Penafsiran dan Bias Ideologi (Kajian Terhadap Konsep Kedaulatan Tuhan Menurut Sayyid Qutb) - Ahlam Irfani (Qur'an and Hadith Academic Society, 2014)
The ideological bias in Qur’anic interpretation cannot be fully eliminated. Its existence, however, cannot be ignored, because it can be reduced. The historical interpretation – considered by some – can respond to this ideological challenge. To prove this statement, this writer will describe Sayyid Qutb’s interpretation in his political concept, especially hakimiyyah or God’s sovereignity in his Fi Zilal al-Qur’an. The ta’wil of Abu Zayd, enriched by the critical discourse analyses and social cognition of van Dijk, will be used to prove that the more ahistorical an interpretation is the more ideological it is.